Factors affecting the implementation of guideline-based prophylactic antiemetic therapy for chemotherapy-induced nausea and vomiting in Japan: a protocol for a hospital-based qualitative study - Yosuke Uchitomi; Junko Saito; Maiko Fujimori; Taichi Shimazu; Ayako Okuyama; Sadamoto Zenda; Ayumu Matsuoka; Akiko Yaguchi-Saito; Yuki Kaji; Miyuki Odawara; Aki Otsuki (BMJ Open)
Introduction Chemotherapy-induced nausea and vomiting (CINV) decrease patients’ quality of life and negatively impact treatment outcomes. Although standard prophylactic antiemetic therapy for acute CINV recommended by guidelines is effective, poor guideline implementation is a worldwide problem. In Japan, prophylactic antiemetic therapy is relatively well implemented for chemotherapy associated with high emetogenic risk, while implementation gaps are observed for that with low emetogenic risk.Although most reports on factors influencing appropriate antiemetic prescription focus on physicians’ attitudes and behaviours, a more comprehensive exploration is needed since chemotherapy is expected to involve pharmacists, nurses and eventually hospital directors. The purpose of this qualitative study is to comprehensively explore the factors that influence the implementation of appropriate prophylactic antiemetic procedures at cancer care hospitals in Japan.Methods and analysis This study is a hospital-based qualitative study using semistructured individual interviews. The target population will be hospital directors, and chiefs (including proxies) of departments of oncology and/or chemotherapy, pharmacy and nursing, working in the hospitals, selected by purposive sampling. We will obtain information on antiemetics in chemotherapy regimens, antiemetic routine use and awareness of guidelines using prequestionnaires. Interviews will then be conducted online using an interview guide. The Consolidated Framework for Implementation Research will be used to collect and analyse the interview data. We will also create new codes inductively, as required. In addition, we will refer to the aggregate results of the Quality Indicator survey to determine the implementation of recommended antiemetic prescriptions for each hospital and discuss the relationship with influencing factors.Ethics and dissemination This study has been approved by the National Cancer Centre Ethics Approval Committee (approval number: 2020-305). The study findings will be disseminated via peer-reviewed journal publications and presentations to academics, policy-makers, and clinicians at scientific conferences.